Analysis of microbial taxonomical groups present in maize stalks suppressive to colonization by toxigenic Fusarium spp.: a strategy for the identification of potential antagonists - Köhl, J.; Lombaers, C.; Moretti, A.; Bandyopadhyay, Ranajit; Somma, S.; Kastelein, P. (Elsevier, 2015)
Pink ear rot of maize caused by Fusarium verticillioides, Fusarium proliferatum and Fusarium graminearum can lead to severe yield losses and contamination of grain with a range of mycotoxins. Maize stalks colonized by Fusarium spp. are the main primary inoculum source for Fusarium incited epidemics in maize or other susceptible crops grown in rotation. The colonization of individual maize stalks originating from fields in The Netherlands, Italy and Nigeria by Fusarium spp. was quantified using specific TaqMan-PCR assays. Highest values were found for F. graminearum and Fusarium avenaceum in Dutch samples, for F. graminearum and FUM producing species (F. verticillioides and F. proliferatum) in Italian samples and FUM producing Fusarium spp. in Nigerian samples. The increase in Fusarium spp. colonization under field conditions during a period of 3–6 months after harvest of the maize crops varied considerably between individual stalks. The fungal and bacterial diversity was analyzed for sub-sets of stalks with high versus low increase of Fusarium colonization. Bacterial taxonomic groups such as Bacillus, Curtobacterium, Erwinia, Flavobacterium, Novosphingobium, Pantoea, Sphingomonas, Rahnella and Staphylococcus and fungal taxonomic groups such as Acremomium sp., Cryptococcus flavescens, Cryptococcus zeae, Leptosphaeria sp. and Microdochium bolleyi were more abundant in the stalks with lower increase in pathogen colonization. Such fungal and bacterial groups associated with ‘suppressive stalks’ may be antagonistic to Fusarium spp. and a source of candidate strains for the selection of new biological control agents.Pink ear rot of maize caused by Fusarium verticillioides, Fusarium proliferatum and Fusarium graminearum can lead to severe yield losses and contamination of grain with a range of mycotoxins. Maize stalks colonized by Fusarium spp. are the main primary inoculum source for Fusarium incited epidemics in maize or other susceptible crops grown in rotation. The colonization of individual maize stalks originating from fields in The Netherlands, Italy and Nigeria by Fusarium spp. was quantified using specific TaqMan-PCR assays. Highest values were found for F. graminearum and Fusarium avenaceum in Dutch samples, for F. graminearum and FUM producing species (F. verticillioides and F. proliferatum) in Italian samples and FUM producing Fusarium spp. in Nigerian samples. The increase in Fusarium spp. colonization under field conditions during a period of 3–6 months after harvest of the maize crops varied considerably between individual stalks. The fungal and bacterial diversity was analyzed for sub-sets of stalks with high versus low increase of Fusarium colonization. Bacterial taxonomic groups such as Bacillus, Curtobacterium, Erwinia, Flavobacterium, Novosphingobium, Pantoea, Sphingomonas, Rahnella and Staphylococcus and fungal taxonomic groups such as Acremomium sp., Cryptococcus flavescens, Cryptococcus zeae, Leptosphaeria sp. and Microdochium bolleyi were more abundant in the stalks with lower increase in pathogen colonization. Such fungal and bacterial groups associated with ‘suppressive stalks’ may be antagonistic to Fusarium spp. and a source of candidate strains for the selection of new biological control agents.